The Impacts of Cardiac Rehabilitation Program on Echocardiographic Parameters in Coronary Artery Disease Patients with Left Ventricular Dysfunction - Masoumeh Sadeghi; Mohammad Garakyaraghi; Mohsen Khosravi; Mahboobeh Taghavi; Nizal Sarrafzadegan; Hamidreza Roohafza (Cardiology Research and Practice)
Introduction. The accurate impact of exercise on coronary artery disease (CAD) patients with left ventricular dysfunction is still debatable. We studied the effects of cardiac rehabilitation (CR) on echocardiography parameters in CAD patients with ventricular dysfunction. Methods. Patients with CAD who had ventricular dysfunction were included into an exercise-based rehabilitation program and received rehabilitation for eight weeks. All subjects underwent echocardiography before and at the end of the rehabilitation program. The echocardiography parameters, including left ventricular ejection fraction (LVEF), LV end-diastolic (LVEDD) and end-systolic diameters (LVESD), and peak exercise capacity measured in metabolic equivalents (METs), were assessed. Results. Seventy patients (mean age = 57.5 ± 10.2 years, 77.1% males) were included into the study. At the end of rehabilitation period, the LVEF increased from 45.14 ± 5.77% to 50.44 ± 8.70% (P<0.001), and the peak exercise capacity increased from 8.00 ± 2.56 to 10.08 ± 3.00 METs (P<0.001). There was no significant change in LVEDD (54.63 ± 12.96 to 53.86 ± 8.95 mm, P=0.529) or in LVESD (38.91 ± 10.83 to 38.09 ± 9.04 mm, P=0.378) after rehabilitation. Conclusion. Exercise training in postmyocardial infarction patients with ventricular dysfunction could have beneficial effects on cardiac function without adversely affecting LV remodeling or causing serious cardiac complications.